PENGUATAN POTENSI LOKAL SEBAGAI BASIS STRATEGI MENGURANGI TINGKAT KEMISKINAN DI DESA IHAMAHU KECAMATAN SAPARUA - Ludwina Pormes; Gilbert Alvin Rumalatu (Jurnal Administrasi Terapan, 2026)
Poverty in rural areas remains a critical challenge in national development. This study aims to analyze how strengthening local potential can reduce poverty levels in Ihamahu Village, Saparua District. The research employs a descriptive qualitative approach using interviews, observations, and documentation. Findings reveal that the utilization of local resources—such as traditional fisheries, dryland farming, and small-scale enterprises rooted in local wisdom—significantly increases household income and reduces dependence on external aid. These results align with the Asset-Based Community Development approach, which emphasizes community-driven empowerment and sustainable strategies for poverty alleviation. In conclusion, strengthening local potential is an effective pathway to community-based poverty reduction and economic resilience. Keywords: Local potential, poverty alleviation, community empowerment, rural development, Ihamahu Village, Saparua District